The winner's curse: Conditional reasoning & belief formation - Christian Koch; Stefan P. Penczynski (University of Mannheim, Department of Economics, 2015)
We investigate the relevance of conditional reasoning and belief formation for the occurrence of the winner's curse with the help of two experimental manipulations. First, we compare results from a very simple common-value auction game with results from a transformed version of this game that does not require any conditioning on future events. In human opponent settings, we observe significant differences in behavior across the two games. Second, we investigate subjects' behavior when they face naïve computerized opponents and after they have faced them. We find that both strong and weak assistance in belief formation changes subjects' play significantly in the auction game. Overall, the results suggest that the difficulty of conditioning on future events is at least as important in explaining frequent occurrences of the winner's curse as is the challenge to form beliefs.
urn:nbn:de:bsz:180-madoc-374751
Keywords: D44; D81; D82; 330; Auctions; Winner's curse; Conditional Reasoning; Beliefs